Predšolski otrok in slikanice - Erženičnik-Pačnik, Marjana (Otrok in knjiga, 1999)
A book should be a child's companion from birth on. It helps him/her get to know his environment and actively participate in it. It is of particular importance that picture books offer children impulses to face their problems, search for solutions, but critically judge them. The selection of a picture book, a fairy-tale, a child's book naturally depends on an adult-parents, grandparents, teachers, librarians and a seller. With our choice we already influence on a child with our beliefs and attitude to the world, what can be even more obvious by the interference of a chosen content. Not only the content, even the manner of our interpretation significantly influences a child's comprehension, on how he/she will think and talk about it. How are the picture books selected in a kindergarten? In order to get my answers I have interviewed more than 50 kindergarten teachers, collected the titles of the most frequently mentioned and read books and analysed some of their contents
Keywords: slikanice; predšolski otroci